Physiological demands or real elite cross-country skiing performances - Carlsson, T.; Carlsson, M.; Hammarström, D.; Tonkonogi, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Introduction: Which are the main physiological differences between a successful and less successful cross-country skier? To our knowledge no previous studies have examined a real elite cross-country ski competition. Main purpose of this study was therefore to validate commonly used test parameters to skiing time and to International Ski Federation (FIS) overall seasonal ranking points and to create multiple regression models to predict skiing performances. Methods: Twelve highly motivated male Swedish national elite cross-country skiers completed a test battery consisting of: isokinetic knee extensor peak torque tests at three different velocities; three different vertical jumps tests; two-part treadmill roller skiing test determining lactate markers, maximal oxygen consumption (VO2max) and time to exhaustion; 60 and 360 s double poling tests determining mean upper-body power (DP60Pmean) (DP360Pmean) and mean oxygen consumption (DP60VO2mean) (DP36VO2mean). Performance data were collected from the Swedish National Championship (SNC) in cross-country skiing (13-17 March 2008): 15-km with individual start in classical technique (SNC15); 30-km double pursuit with mass-start (SNC30); sprint prolog in free-style technique (SNCsprint). In addition to ski races, overall seasonal ski ranking points were collected from FIS 3rd Cross-Country Points List 2007/2008 published before SNC for distance (FISdist) and sprint (FISsprint) races. Correlations between test parameters and performance data were established using Pearson´s correlation analysis. Prediction models were created using standard multiple linear regression analysis. Results: Time to exhaustion during the incremental treadmill roller ski test is best correlated with both SNC15 (r = -0.86, p < 0.001) and SNC30 (r = -0.81, p < 0.01). For SNC15 significant correlations were shown with VO2max both absolute and relative to body weight, lactate markers, DP60Pmean and DP60VO2mean. Corresponding correlations for SNC30 were: lactate markers, DP60VO2mean and percentage decrease in mean knee extension peak torque when comparing highest and lowest velocities. Highest correlation coefficient for SNCsprint was found for DP60Pmean (r = -0.93, p < 0.05). Significant correlations for SNCsprint was also detected for DP360Pmean as well as DP360VO2mean and jump height in squat jump. Prediction models explain 68, 91, 68, 77 and 82% of the variance in performance for SNC15, SNC30, SNCsprint, FISdist and FISsprint, respectively. Discussion: Correlations found in this study have validated several commonly used physiological tests with real elite cross-country skiing performances. Frequently investigated test parameters like VO2max and anaerobic thresholds are of great importance for success in cross-country skiing. Many recent research studies have focused on upper-body capacity and we could confirm that high mean power production in double poling is necessary to be successful as elite skier in both sprint and distance races.